PERENCANAAN PEMBELAJARAN BAHASA ARAB DI PERGURUAN TINGGI PARIWISATA - Ernawati, Euis (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2018)
This study aims to analyze the lesson plans of Arabic teaching-learning in STIE Pariwisata YAPARI. The researcher hopes that this research can describe the Arabic teaching-learning concept in tourism College. The research uses qualitative approach with descriptive analysis. The research subjects were an Arabic lecturer, and 11 students on their fourth semester. The data were collected by interview and document analysis as triangulation. The result showed that the planning of Arabic teaching-learning can be categorized as good. The vision-mission of institution, curriculum, lesson plan, and academic management were connected well. There were some problems: The campus had no written guideline of lesson plans writing and less of credit semester system. The recommendations of this research were: the campus should make guideline of lesson plans writing and the addition of the number of credit semester system.